Who Survives and Who Does Not? The Rise and Decline of Personalized Parties. Issue 1 (February 2022) - Yovcheva, Teodora
The analysis of parties created around charismatic leaders is becoming more important in dynamic times when the mainstream parties are challenged by outsiders. Most of the research on personalized parties focuses on Western Europe although the phenomenon has significant implications for East European party systems. This article examines the development of two highly electorally successful personalized parties in Bulgaria: National Movement Simeon the Second (NDSV) and Citizens for European Development of Bulgaria (GERB), the incumbent ruling party. Their similar success but different paths of development provide a good basis for examining the stabilizing factors of personalized parties. The article fills a gap in the theoretical field by using information from qualitative interviews with high-level party members and proves that adoption of an organizational strategy is the key factor for survival. Examining a case of the emergence of personalized parties, the research finds that alongside charismatic leaders, investment in local branches and representation in localities are stabilizing factors when the popularity of the leader decreases and in this way secure the more stable development of the party.